(untitled) (African Journal of Biomedical Research, 2022)
The main control strategy against Newcastle disease in most endemic countries is to routinely vaccinate birds at various stages of their developmental life cycle. This study was conducted to compare the immune response in chicks vaccinated using the Old (1980) and New (2017) vaccination regimes for Newcastle disease in commercial layer production in Ghana. The study also evaluates the mortality rate and cost involved associated with both vaccination regimes. Clinical features, mortality and cost involved were recorded while blood samples were collected at weeks 1, 4, 8, and 18 of age for birds in group A and weeks 1, 4, 6, 12 and 18 of age for birds in group B and antibody titres of the birds were determined using haemagglutination-Inhibition test and the geometric mean titres were calculated. There was no significant difference in antibody titres among the two groups. Antibody titres increased appreciable from week 1 to week 18 in both groups. The mortality was higher (41) in the old vaccination regime as compared to the new vaccination regime (35). The cost involved in vaccinating birds using the old (1980) vaccination regime was lower (by week 16) than the new (2017) vaccination regime. In conclusion, there was no appreciable advantage of the new vaccination regime over the Old in terms of antibody titre, mortality except cost involved.